Measuring Nurses’ Knowledge and Awareness of Climate Change and Climate-Associated Diseases: Systematic Review of Existing Instruments - Omar Portela Dos Santos; Élodie Perruchoud; Filipa Pereira; Paulo Alves; Henk Verloo (Nursing Reports)
Background: As early as 1995, the Institute of Medicine suggested that nurses were inadequately prepared for and educated about climate change and its health consequences. The aim of this systematic review is to identify the most reliable, robust, and valid instruments for measuring nurses’ knowledge and awareness of climate change and climate-associated diseases. Methods: Included studies were appraised using the Mixed-Methods Appraisal Tool and the Appraisal tool for Cross-Sectional Studies. The psychometrics and clinimetrics of the instruments were evaluated using the COSMIN Risk of Bias checklist and the COSMIN methodology for assessing content validity. Results: Medline, PubMed, Embase, CINAHL Ebesco, Cochrane Library Wiley, Web of Science Core Collection, Trip Database, JBI OVID SP, GreenFILE EBSCO, Google Scholar, ProQuest Dissertations and Theses Global, and DART-EU were consulted. The 14 studies retained identified eight different instruments evaluating attitudes, perceptions, environmental awareness, environmental sensitivity, environmental attitudes, behaviours, motivation, concern, optimism, and experience. This review is reported according to the PRISMA guidelines. Conclusions: The New Ecological Paradigm Scale (NEPS) and the Climate, Health, and Nursing Tool (CHANT) are the most reliable, robust, and valid instruments for measuring nurses’ knowledge and awareness of climate change and climate-associated diseases.